Geohistória do turismo em Sabará, Caeté e Nova Lima: uma ferramenta ao planejamento - Guilherme Maximiano Ferreira Santos; Tainara do Carmo Lopes da Silva; Luiza Souza Pereira; Larissa Alves de Lira (Confins)
This article sought to contrast the urban forms and functions assumed from a long-term regional and geo-historical context in three case studies in the metropolitan region of Belo Horizonte with the spatiality of tourism. Thus, it sought to observe which the tourist refunctionalization pattern regarding these forms and functions. It is concluded that some historical processes have become essential for the development of contemporary tourism: the historical heritage, planning and the gradual transformation of landscapes by economic activities, i.e., a controlled use of resources, so that the negative effects of long-term economic exploitation of a territory can in the future be used or reversed by the new tourist functions assumed.